ANXIETY AND DEPRESSION IN INTERNAL MEDICINE - A. V. Fedotova (Рациональная фармакотерапия в кардиологии, 2016)
The problem of anxiety and depression in internal medicine is discussed. Diagnosis of these disorders in general practitioner every day practice is surveyed. Possibilities of anxiety and depression treatment are highlight. Modern psychopharmacotherapy is focused, especially antidepressants usage.